Halo structure investigation of nucleus 8He via core deformation parameter - Fitri Hakeem M. Salih,; Jobaidul Islam,; Shahidan Radiman,; Khoo, Kok Siong (Penerbit Universiti Kebangsaan Malaysia, 2020)
Helium-8 (8He) is a four neutrons halo nucleus and is the halo nucleus that attract attention to observe because it belongs to the group of light dripline nuclei. We studied the two neutrons halo nucleus of 8He. This halo nucleus lies on the neutron rich dripline in the nuclear landscape. Nucleus 8He was investigated in the Three-body Model with two different configurations (T and Y). To describe the Three-body Model, Jacobi coordinate systems for few bodies was used for this hyper-nucleus (8He). In this study, core (6He) + two valence neutrons (n + n) were considered as the Three-body. Based on the finding, theoretical data on configuration Y met a good agreement with the experimental data of binding energy and rms matter radius. While for configuration T, the data slightly differ from the experimental data. The results showed that the core deformation parameters, β2 of 8He were 0.12, 0.19, 0.35, 0.40, and 0.47. The binding energies -3.112 MeV, -3.416 MeV, and -3.625 MeV were calculated for the deformation parameters 0.35, 0.40, and 0.47 and rms radii 2.032 fm, 2.305 fm, and 2.39 fm were found for the deformation parameters 0.19, 0.35, and 0.4, respectively. In conclusion, 8He exhibits in prolate due to positive values of core deformation parameters.